The anarchical society a study of order in world politics - Bull, Hedley (Columbia University Press, 1977)
The Anarchical Society is one of the masterworks of political science and the classic text on the nature of order in world politics. Originally published in 1977, it continues to define and shape the discipline of international relations. This edition has been updated with a new, interpretive foreword by Andrew Hurrell